2003
DOI: 10.1590/s0102-311x2003000200011
|View full text |Cite
|
Sign up to set email alerts
|

Concentração residual de hexaclorociclohexano em área contaminada na Cidade dos Meninos, Duque de Caxias, Rio de Janeiro, Brasil, após tratamento com óxido de cálcio

Abstract: Os hexaclorociclohexanos (HCHs) são atualmente considerados carcinógenos humanos. No Brasil, uma severa contaminação de solo causada por HCHs é observada na Cidade dos Meninos, Duque de Caxias, Rio de Janeiro, onde uma antiga fábrica desses compostos foi abandonada há quarenta anos, ameaçando seus 1.700 habitantes. Para remediar a área pesadamente contaminada (área foco), um tratamento com óxido de cálcio foi realizado. Análises de solo coletadas superficialmente na área tratada, anos após o tratamento, mostra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…A close analysis revealed that the LinB enzymes of Spϩ and UT26 differ from each other by three amino acids and that LinB of B90A differs from those of Spϩ and UT26 by six and seven amino acids residues, respectively. These differences in amino acids are outside the putative catalytic domain (D-108, H-272, and E-132) (7,11,17,18,22,27,28,33,34,37,40,47), but they seem to play an important role in the substrate specificity of the enzymes. Although the studies with purified LinB proteins from B90A and Spϩ are preliminary, they strongly indicate that strain B90A is best suited for biodegradation of ␤-HCH, the most recalcitrant isomer.…”
Section: Discussionmentioning
confidence: 99%
“…A close analysis revealed that the LinB enzymes of Spϩ and UT26 differ from each other by three amino acids and that LinB of B90A differs from those of Spϩ and UT26 by six and seven amino acids residues, respectively. These differences in amino acids are outside the putative catalytic domain (D-108, H-272, and E-132) (7,11,17,18,22,27,28,33,34,37,40,47), but they seem to play an important role in the substrate specificity of the enzymes. Although the studies with purified LinB proteins from B90A and Spϩ are preliminary, they strongly indicate that strain B90A is best suited for biodegradation of ␤-HCH, the most recalcitrant isomer.…”
Section: Discussionmentioning
confidence: 99%
“…Note that ␣-HCH also exists in two enantiomeric (ϩ and Ϫ) forms. 50,000 tons in Brazil (38), Canada (135), Germany (159,183), Spain (26,29,181), India (30,139), and the United States (135). HCH-degrading sphingomonads have been recovered in six countries in Europe and Asia, although precise locations are often not reported (see text).…”
Section: Introductionmentioning
confidence: 99%
“…Literature provides evidence on some heavy contamination episodes by HCH due to formulation factories and their illegal muck dumping (Table 1). Such HCH dumpsites have been found all over the world and have been reported from Brazil (Rio de Janeiro; Oliveira et al 2003); Spain (Pontevedra; Concha-Grana et al 2006;Vega et al 2007), Bilbao (Mohan et al 2006); Germany (Chemnitz; Boltner et al 2005; Bitterfeld; Kalbitz and Popp 1999;Wycisk et al 2003); the US (North Carolina; Earth fax 2002), and India (Lucknow; CAPE http://www.panna.org/ campaigns/docsLindane/lindaneDirtySecret.pdf). In Galicia (Spain), the stores of a pesticide factory located in the industrial estate of Torneiros until 1964 caused the contam- Philips et al (2006) ination of an area of 45,000 m 2 affecting the soils and aquifer (Concha-Grana et al 2006).…”
mentioning
confidence: 99%